Kajian Representasi Tubuh dalam Film Fiksi Ilmiah - Rabendra Yudistira Alamin; Alvanov Zpalanzani Mansoor; Pindi Setiawan (Wimba : Jurnal Komunikasi Visual, 2011)
The development of informatics technology in the 21st century has changed the world as if there is no limit and distance. Communication process has been done through various avatar medium which replaces the presence of human body. Representation has become the main factor to visualize or to create an image of human being towards the universe. Surrogates is a science fiction movie which is presenting the representation of different kinds of thoughts and imagination about how life will be conducted in the future or when mankind will have got the avatar technology of human body which is exactly the same as the person that it is represented. Surrogates, this movie is trying to recreate and represent the fact through representation of human body packed in audio visual language. The purpose of this research is to analyze the body representation of a movie to communicate the message to the audience. The theory is based on film studies and the main question about representation is how the world is constructed and represented through the film media. The approach to study the movie is dynamic picture analyzation based on visualization theory. This approach gives the writer an opportunity to break down the component in a movie into smaller units of representation. According through this research, the writer has concluded that the robot 'body' on Surrogates has completely represented the perfection body of human beings in the 21st century. Appearances and behavior of human body has been successfully sent the message to the audience about the story of this movie. By the end of this research, the writer has described the variable of body sign representation in the movie as a unity, so that the writer can decide the components and structures to create it.